A Review on Cloud Computing Security - Marry Teo; Hairulnizam Mahdin; Lee Jia Hwee; Haezel Ann Dicken; Tay Xin Hui; Teng Mee Ling; Mohd Sanusi Azmi (Politeknik Negeri Padang, 2018)
Cloud computing is a technology that maintain the data and application by using the central remote server with the internet connection. By utilizing cloud computing, user can reduce their costs as they no need to purchase their own hardware and software. However cloud computing still has many issues concerning securities, such as privacy issues, loss of data and stolen of data. Some security issues over cloud services including confidentiality, integrity, availability, privacy and attacks are concerned by the users. This paper reviews some of the issues and its current solutions.